High temporal variability of wintertime fog, aerosol and Red-Blue-Ratio using ground-based observations of shortwave irradiance and sky imagery over a station in Indo-Gangetic Basin: Optical and Radiative characteristics. (1st April 2020) - Sunil, Sneha; Padmakumari, B.
Abstract: Winter Fog over the Indo Gangetic Basin (IGB) has drawn great attention during the recent decades due to its intense and prolonged episodes and having severe impact on the socio-economic aspects of the Indian sub-continent. In this study a simple methodology is used to retrieve day time fog, aerosol and Red-Blue Ratio (RBR) at a high temporal resolution of 1 min using the surface shortwave irradiance (Rs ) from the Multifilter Rotating Shadowband Radiometer (MFRSR) and real-time sky images from the Total Sky Imager (TSI) during December 2014 and January 2015 over a station Varanasi in IGB. RBR distinguishes the sky condition from clear-haze-fog/cloud. The frequency of occurrence of fog per hour and per month is higher in January as compared to December and most of the time cloud fraction (CF) > 80%, Rs  < 200 W/m 2 and RBR is high. INSAT-3D satellite fog product at half hourly interval is comparable with the retrieved fog. The aerosol and fog optical depths (AOD, FOD, respectively) also retrieved from Rs measurements revealed high AODs/haze before and after the fog, consisting of smoke, dust and polluted dust as revealed from CALIPSO satellite, and high FODs during the prolonged and intense fog events. The high frequency measurements revealed frequent variability in FOD during the passage of the Western Disturbances (WD) resulting in the advection fog. The surface shortwave radiative forcing (SWRF) due to fog revealed high temporal variability from −100W/m 2 to −300W/m 2 and the magnitude of negative forcing or cooling effect increased with increase in FOD, while aerosol forcing varied up to −50 W/m 2 for clear skies and up to −100 W/m 2 for high AODs/haze. Highlights: A new approach to retrieve day time fog using high frequency ground-based SW irradiance and sky imagery. High temporal variability of winter fog, aerosol and RBR. RBR distinguishes the sky condition from clear-haze-fog/cloud. High values of FOD reveal intense and prolonged events during day time. SWRF due to fog and aerosol increased with increase in optical depths.